2016
DOI: 10.1063/1.4967374
|View full text |Cite
|
Sign up to set email alerts
|

Role of film stoichiometry and interface quality in the performance of (Ba,Sr)TiO3 tunable capacitors with high figures of merit

Abstract: Parallel plate capacitors with quality factors exceeding 1000 were fabricated using Ba0.3Sr0.7TiO3 (BST) thin films grown by hybrid molecular beam epitaxy on epitaxial Pt bottom electrodes. The influence of film stoichiometry was investigated by varying the (Ba + Sr)/Ti ratio around the stoichiometric composition. The quality factor is highest for stoichiometric films, but (Ba + Sr)-rich films can be biased to higher fields. Furthermore, two different processes were used to deposit the top electrodes of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[159] RHEED was found to exhibit a c(4×4) reconstruction, similar to reports of SrTiO 3 , [131] however, on relaxed Ba 0.30 Sr 0.70 TiO 3 films the surfaces were found to contain additional crystalline phases when grown under both, stoichiometric and non-stoichiometric conditions. [215] The films were fully relaxed, and it was found that the lattice parameter linearly changed with composition x, as shown in Figure 27 samples. [216] In contrast, the quality factor for hMBE grown Ba 1-x Sr x TiO 3 larger than 1000 was found.…”
Section: Quaternary Perovskites: a 1-x A' X Bo 3 And Ab X B' 1-x Omentioning
confidence: 96%
See 1 more Smart Citation
“…[159] RHEED was found to exhibit a c(4×4) reconstruction, similar to reports of SrTiO 3 , [131] however, on relaxed Ba 0.30 Sr 0.70 TiO 3 films the surfaces were found to contain additional crystalline phases when grown under both, stoichiometric and non-stoichiometric conditions. [215] The films were fully relaxed, and it was found that the lattice parameter linearly changed with composition x, as shown in Figure 27 samples. [216] In contrast, the quality factor for hMBE grown Ba 1-x Sr x TiO 3 larger than 1000 was found.…”
Section: Quaternary Perovskites: a 1-x A' X Bo 3 And Ab X B' 1-x Omentioning
confidence: 96%
“…[212] Ba 1-x Sr x TiO 3 films were grown on SrTiO 3 after sputter deposition of 100-nm-thick epitaxial Pt layers used as bottom electrode. [212,215] Stoichiometric conditions were identified from the minimum out-of-plane lattice parameter for the compositions x = 0.19, 0.30, 0.35, 0.46. While this criteria is consistent with the stoichiometric condition of SrTiO 3 films [98] , it differs from that of BaTiO 3 .…”
Section: Quaternary Perovskites: a 1-x A' X Bo 3 And Ab X B' 1-x Omentioning
confidence: 99%
“…The trade-off between Q and n has long been stymieing the application of BST x -based tunable capacitance devices. Much effort has been devoted to innovating the Sr m+1 Ti m O 3m+1 Ruddlesden−Popper phase crystal structure 10,11 and utilizing the hybrid molecular beam epitaxy growth of defect-free high-quality BST x thin films 12,13 to extend their frequency limitations and figure of merits 14,15 by suppressing dielectric losses from local defects, 16 degenerate phonon distributions, 17,18 and polar regions in nanoscale. 19,20 Recently, a fundamentally distinct approach has been put forward to enhance the dielectric responses by the introduction of ferroelectric nanodomain structures in a Ba 0.8 Sr 0.2 TiO 3 (BST 0.8 ) thin film slightly below the Curie transition temperature, realizing an order of magnitude increase of n and high Q values simultaneously facilitated by the ferroelectric domain-wall fluctuation at room temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the performance of ferroelectric phase shifters and tunable filters is usually measured by the tunability (T r ) and quality factor (Q F ). Their definitions are as follows [12][13][14] T…”
Section: Introductionmentioning
confidence: 99%